Association Of Nitrogen-Fixing Bacteria In Rice - Muhammad, Muhammad; Sulistyowati, Liliek; Widayati, Wiwik E; Parwito, Parwito (SINTA Journal (Science, Technology, and Agricultural), 2022)
The research was aimed first: to understandability of GFP marker (green fluorescent protein) gave identities nitrogen-fixing bacteria that clear as endophytic when was the application to plant tissue. The research was aimed second: to understandability of nitrogen-fixing bacteria make special colonization as endophytic use Seed dressing method and Dipping method. The results of the research are GFP markers that show its ability to provide a clear identity as an endophytic bacterium when applied in natural microbial communion. Besides that, GFP is also stable in the applications on rice plant tissue and is able to provide a fairly clear expression. The bacteria Azospirillum lipoferum-1224, Azospirillum lipoferum-1247, Azorhizophilus paspali-2283, Azotobacter chroococum-2286 were able to colonize the rice plant tissue using either the inoculation method of Dipping or Seed dressing.